Histological analysis after arm tip amputation in the brittle star Ophioplocus januarii (Echinodermata: Ophiuroidea). - Di Giorgio, Gisele (2015)
Wound healing in the arm tip after amputation in the brittle star Ophioplocus januarii was examined in San José gulf, Argentina, to observe histological and morphological changes. The process of wound healing is described and compared with other brittle stars species. This process in O. januarii involves the closure of the wound, the repair of the tissue damage and posterior formation of a presumptive stalked blastema by undifferentiated cells, sclerocytes and presumptive blastemic cells. The sclerocytes are the most abundant cell type due to this cells are crucial to the future skeleton regeneration. The results found in this study support the results found in others brittle stars.